A network model to optimally group road maintenance interventions for work zone development. Issue 7 (3rd July 2023) - Xu, Zhepu; Burkhalter, Marcel; Adey, Bryan T.; Yang, Qun
Abstract: One of the main tasks of road managers is to plan maintenance interventions, which is currently in practice often done using a simple ranking-based method. However, an increasing number of researchers are focusing their efforts on supporting the planning process using operations research models. Models that have been developed can optimally group maintenance interventions: (1) in a single work zone, taking into consideration both work zone and asset related costs, and (2) in multiple work zones, taking into consideration only asset-related costs. In this paper, a new operation research model is developed to optimally group maintenance interventions in multiple work zones, taking into consideration both work zone and asset-related costs. The new model is used to optimally group maintenance interventions for a road network located in Fujian province in China. The improvement obtained from using the new model is compared to the result determined using an operation research model that can only determine one optimal group of intervention at a time, and one determined using a commonly used ranking-based method. It is shown that the new model results in the highest net-benefit, and that both operation research models result in higher net benefits than the ranking-based method.